Cardiac mechanics in response to proteasome inhibition: a prospective study. (18th August 2022) - Makris, Nikolaos; Georgiopoulos, Georgios; Laina, Aggeliki; Tselegkidi, Maria-Eirini; Fotiou, Despoina; Kanellias, Nikolaos; Eleftherakis-Papaiakovou, Evaggelos; Migkou, Magda; Papanagnou, Eleni-Dimitra; Katogiannis, Konstantinos; Petropoulos, Ioannis; Anninos, Hector; et al.
Abstract: Aim: Ubiquitin-Proteasome System (UPS) is of paramount importance regarding the function of the myocardial cell. Consistently, inhibition of this system has been found to affect myocardium in experimental models; yet, the clinical impact of UPS inhibition on cardiac function has not been comprehensively examined. Our aim was to gain insight into the effect of proteasome inhibition on myocardial mechanics in humans. Methods and results: We prospectively evaluated 48 patients with multiple myeloma and an indication to receive carfilzomib, an irreversible proteasome inhibitor. All patients were initially evaluated and underwent echocardiography with speckle tracking analysis. Carfilzomib was administered according to Kd treatment protocol. Follow-up echocardiography was performed at the 3rd and 6th month. Proteasome activity (PrA) was measured in peripheral blood mononuclear cells. At 3 months after treatment, we observed early left ventricular (LV) segmental dysfunction and deterioration of left atrial (LA) remodelling, which was sustained and more pronounced than that observed in a cardiotoxicity control group. At 6 months, LV and right ventricular functions were additionally attenuated ( P < 0.05 for all). These changes were independent of blood pressure, endothelial function, inflammation, and cardiac injury levels. Changes in PrA were associated with changes in global longitudinal strain (GLS), segmental LV strain, and LA markers ( P < 0.05 for all). Finally, baseline GLS < −18% or LA strain rate > 1.71 were associated with null hypertension events. Conclusion: Inhibition of the UPS induced global deterioration of cardiac function. Graphical Abstract: Graphical Abstract Cardiac markers change at 3 and 6 months after Kd treatment and their association with PrA. Carfilzomib induced a global deterioration of cardiac function, with LA remodelling markers and LV strain segmental score deteriorating earlier.